2017
DOI: 10.1002/1878-0261.12083
|View full text |Cite
|
Sign up to set email alerts
|

EMT and MET: necessary or permissive for metastasis?

Abstract: Epithelial‐to‐mesenchymal transition (EMT) and its reverse mesenchymal‐to‐epithelial transition (MET) have been suggested to play crucial roles in metastatic dissemination of carcinomas. These phenotypic transitions between states are not binary. Instead, carcinoma cells often exhibit a spectrum of epithelial/mesenchymal phenotype(s). While epithelial/mesenchymal plasticity has been observed preclinically and clinically, whether any of these phenotypic transitions are indispensable for metastatic outgrowth rem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
211
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(229 citation statements)
references
References 146 publications
5
211
0
2
Order By: Relevance
“…The potential relevance of EMT to metastasis is largely based on in vitro studies using transformed epithelial cells and experimental manipulations. [59] Tumors consist of genetically unstable cells and infiltrating cells could contribute to shifts in linage markers. The gain or loss of markers seems insufficient to assume a whole-scale gene expression reprogramming of a cell type.…”
Section: Emtmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential relevance of EMT to metastasis is largely based on in vitro studies using transformed epithelial cells and experimental manipulations. [59] Tumors consist of genetically unstable cells and infiltrating cells could contribute to shifts in linage markers. The gain or loss of markers seems insufficient to assume a whole-scale gene expression reprogramming of a cell type.…”
Section: Emtmentioning
confidence: 99%
“…[59] The EMT is primarily considered a phenomenon of the in vitro environment. [60] It is not clear whether alternative regulatory programs can also enable EMT-like capability.…”
Section: Emtmentioning
confidence: 99%
“…However, several studies have shown that disseminated cancer cells in metastatic sites are more like epithelial cells compared to cancer cells in primary tumors in a number of different types of carcinomas, including prostate cancer, breast cancer, colorectal cancer, pulmonary cancer and hepatic carcinomas. To explain this contradiction, a MET process was assumed to be involved in the formation process of metastatic tumors [4,5]. Epigenetic regulation of metastasis suppressor genes promises to be a potentially important mechanism by which dietary components can moluate cancer metastasis since many phytochemicals are known to modulate gene expression [4,6,7].…”
Section: Cancer Metastasismentioning
confidence: 99%
“…It is a very important cancer-preventing mechanism to epithelial tissues because anoikis mechanism facilitates the elimination of unattached epithelial cells, which have been shed from the epithelium in the high-rate epithelium turnover process, to prevent these cells from attaching to inappropriate sites. Inappropriate attachment may lead to extensive neoplastic growth and cause cancers [5,8,9].…”
Section: Emt and Anoikismentioning
confidence: 99%
See 1 more Smart Citation